INOVASI DALAM PENINGKATAN PELAYANAN KEPENDUDUKAN PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN ENDE PROVINSI NUSA TENGGARA TIMUR - Aristo Gude kesu (PRAJA observer: Jurnal Penelitian Administrasi Publik (e- ISSN: 2797-0469))
The purpose of this study was to determine the service innovations provided by the Department of Population and Civil Registry of Ende Regency, East Nusa Tenggara Province. In this study the authors used descriptive qualitative research methods. The focus of this research is the implementation of innovation in making E-KTP, KK, Deed, Death Certificate, Divorce Certificate and others and the supporting and inhibiting factors of the ijovasi. The primary data source in this study is the government apparatus of Ende Regency which is related to the management of population administration, namely the Population and Civil Registry Office of Ende Regency, East Nusa Tenggara Province. Meanwhile, the information in this research is the employees of the Population and Civil Registry Office of Ende Regency, East Nusa Tenggara Province and the people who take care of changes to E-KTP, KK, Deed, Death Certificate. Data were collected through interviews, observation and documentation. The data analysis technique used is to process and interpret the data. Based on the results of the study, it can be concluded that service innovations in making E-KTP, KK, Deeds, Death Certificates, Divorce Certificates and others at the Population and Civil Registry Office, Ende Regency, East Nusa Tenggara Province show that GARUGIWA innovations and Additional Working Time can create excellent service. These innovations have many advantages and some of them can shorten the time and quickly. However, the GARUGIWA innovation and Additional Working Time also have an inhibiting factor, namely the low network connection so that it can become an obstacle to the success of an innovation.